Naturally Derived Photoinitiators for Dental and Biomaterials Applications - Abdul-Monem, Mohamed Mahmoud (European Dental Research and Biomaterials Journal, 2020)
Biocompatibility of materials used in dental and biomaterials applications is very important and depends on the components of these materials. Photopolymerized materials for dental and biomaterials applications have been progressively used since the 1970s. One of the crucial components in these materials is the photoinitiator (PI) that initiates the polymerization reaction. Synthetic PIs are the most commonly used types, but owing to their drawbacks such as cytotoxicity, insolubility in water, and high cost, research on naturally derived (bio-sourced) PIs is growing, to find an alternative to these synthetic types, especially in the growing field of three-dimensional (3D) printing and bioprinting of biomaterials for tissue engineering applications. Naturally derived PIs are biocompatible, highly water-soluble, and abundant. Naturally derived PIs have been used to prepare experimental dentine bonding agents, dentine primers, photo-crosslinked hydrogels for tissue engineering applications, antibacterial coatings, guided tissue regeneration membranes, and 3D printed biomaterials. An electronic search was done using MEDLINE/PubMed and Scopus databases using the keywords naturally derived, bio-sourced, PIs, dental, biomaterials, 3D printing, and 3D bioprinting, to review potential naturally derived PIs for dental and biomaterials applications. There are a variety of naturally derived PIs with various colors and absorption spectra to choose from, according to the intended application. Most of naturally derived PIs can be used with modern conventional dental light curing units, making them applicable for experimental studies for potential dental and biomaterials applications. Due to their biocompatibility and availability it is expected that in the upcoming years, research on naturally derived PIs and their dental and biomaterials applications will increase especially in the growing field of 3D bioprinting in which cell viability is essential; thus this review was done.
Keywords: naturally derived; bio-sourced; photoinitiators; dental; biomaterials; 3D printing; 3D bioprinting